Social support may prevent self‐cutting in adolescence: A 5‐year follow‐up study. Issue 4 (24th June 2021) - Rissanen, Marja‐Liisa; Kekkonen, Virve; Kraav, Siiri‐Liisi; Kivimäki, Petri; Laukkanen, Eila; Hintikka, Jukka; Tolmunen, Tommi
Abstract: Self‐cutting is common among adolescents. However, studies examining protective factors are rare. It has been suggested that social support may protect against self‐cutting in adolescence. The aim of this study was to investigate the possible association of social relationships with the initiation of self‐cutting. Methods: The participants were community‐dwelling Finnish adolescents ( N  = 4171) aged 13–18 years at baseline. The follow‐up assessment was conducted 5 years later ( N  = 794). Those adolescents who had self‐cut before the baseline assessment ( N  = 134) were excluded from the analysis, leaving a total of 660 participants to be analyzed. In this group, 37 adolescents initiated self‐cutting during the 5‐year follow‐up period and 623 did not. Cox's proportional hazards models were used with several adjustments for possible confounding factors. Findings: A higher age, male gender, good relationships with siblings, weekly meetings with friends, and personal experience of not being lonely associated with the noninitiation of self‐cutting during the follow‐up period. Good relationships with parents or peers had no association with the initiation of self‐cutting. Depressive symptoms mediated the effect of subjective loneliness on initiating self‐cutting. Conclusions: Social support produced by friends may have a protective effect against self‐cutting.